Charitable Behavior of Muslim in Indonesia during the COVID-19 Pandemic: A Tobit Model Analysis - Agni Alam Awirya; Indah Piliyanti; Dian Novita (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The COVID-19 pandemic has caused a decline in social welfare. In such a situation, community philanthropy, including from the Muslim community, becomes critical. This study aims to explore the charitable behavior of Muslims in Indonesia during the COVID-19 pandemic. The Tobit regression was used to analyze data from online surveys to determine the pattern changes of donations during the pandemic as well as the factors affecting the amount of donation. This study uncovered that Zakat Management Organizations (BAZNAS and LAZ) were some of the main choices for distributing zakat and alms (sedekah) during the pandemic. It was found that the factors with a positive and significant effect on the probability of increasing the percentage of donations were education, length of stay, and expenses. The results of this study contribute to the policy of developing the Zakat Management Organization as institutions trusted by the community in distributing zakat funds. This study supports the fundraising of the zakat organizations in terms of offering valuable insights and clear description about the Indonesian people’s charitable behavior. More importantly, this study suggests that improving the quality of education is crucial to increase community awareness in performing Islamic philanthropy such as giving zakat, sedekah, and waqf.